PEMBERDAYAAN BANK SAMPAH BERBASIS SISTEM INFORMASI ONLINE (SiOn) - Nurjanah, Adhianty; Sakir, Sakir (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2019)
The lack of public awareness and knowledge of the importance of managing household waste independently through a waste bank; The unavailability of an online information system that functions as communication, information and education related to the management of waste banks; Do not have promotional media for krajinan products originating from household waste; The lack of support from the village government in managing waste independently through this waste bank is a problem that occurs in garbage banks located in RW 17 Kradenan, Banyuraden Village, Gamping District, Sleman Regency, DIY. Based on these problems, this community service aims to empower the Kradenan Berseri waste bank through an online-based information system (SIOn). The use of online-based information systems (SIOn) will have an impact, waste banks are able to adapt quickly to stakeholder needs. In addition, this online-based information system (SIOn) can be used as a media for promotion and education as well as literacy related to the importance of managing household waste through waste banks to the public.